2020
DOI: 10.7150/ijms.48456
|View full text |Cite
|
Sign up to set email alerts
|

Shorter Leukocyte Telomere Length coupled with lower expression of Telomerase Genes in patients with Essential Hypertension

Abstract: Background: The essential hypertension (EH) pathophysiology remains poorly understood. Many studies indicate that reduced leukocyte telomere length (LTL) is involved in the EH pathogenesis, however, the direct analysis of arterial telomere length (ATL) from EH patients and normotensive individuals did not show a difference. To address these discrepant observations between LTL and ATL, we performed comprehensive analyses of LTL, telomerase gene expression and their genetic variants in healthy normotensive contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…The analysis of this lncRNA on 3 samples of PBMCs via RNA-Flow demonstrated the detection of this RNA was possible in cells derived from blood samples (Fig. 2d ) as previously shown via RT-qPCR 18 , 19 . Quantification in 3 biological samples in PBMCs showed positive cells with average fluorescence intensity of 146 ± 3.2 MFI when compared to control cells with an average mean of 45.7 ± 2.4 MFI.…”
Section: Resultssupporting
confidence: 73%
“…The analysis of this lncRNA on 3 samples of PBMCs via RNA-Flow demonstrated the detection of this RNA was possible in cells derived from blood samples (Fig. 2d ) as previously shown via RT-qPCR 18 , 19 . Quantification in 3 biological samples in PBMCs showed positive cells with average fluorescence intensity of 146 ± 3.2 MFI when compared to control cells with an average mean of 45.7 ± 2.4 MFI.…”
Section: Resultssupporting
confidence: 73%
“…For instance, some previous studies suggested that there was no association between TL and blood pressure (38)(39)(40). A previous meta-analysis of 10 studies indicated a significant negative correlation between TL and hypertension (41), which was also observed in recent studies (42)(43)(44)(45). However, it has also been reported that longer TL is associated with higher blood pressure (46,47).…”
Section: Discussionmentioning
confidence: 62%
“…We showed that BPH prostate tissue had the longest telomeres, which might explain why apoptosis and cell death are not initiated. Hyperplasia is caused when cell count increases in the organ, which should cause shorter telomeres in BPH (as cells divide more frequently) as in the literature described (Cheng et al, 2020;Sommerfeld et al, 1996). However, in our and another study, BPH had the longest telomeres compared with normal or cancerous tissue (Heaphy et al, 2010).…”
Section: Discussionmentioning
confidence: 98%